2001
DOI: 10.1002/app.1314
|View full text |Cite
|
Sign up to set email alerts
|

TTT and CHT curing diagrams of water‐borne polycondensation resins on lignocellulosic substrates

Abstract: Lignocellulosic substrates such as wood were found to have a marked modifying influence on both lower temperature and higher temperature zones of TTT and CHT diagrams during hardening of phenol-resorcinol-formaldehyde (PRF) and melamime-urea-formaldehyde (MUF) polycondensates. Although the modifying influence of the substrate on the higher temperature zone of CHT diagrams presented the same trend of what was already reported for phenol-formaldehyde (PF) and ureaformaldehyde (UF) polycondensates, marked differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
1
11
0
2
Order By: Relevance
“…The gelation and vitrification curves are the most characteristic features of both TTT and CHT diagrams; the S‐shape of the CHT diagram, in particular, defines the region at which the reaction rate is greatly reduced because diffusion control becomes more pronounced in the glass‐transition region. Although the majority of the CHT and TTT diagrams studies reported to date have mostly focused on the curing of epoxy resins on glass fiber braid,1–5 CHT and TTT diagrams of other polycondensation resins used in considerable amounts as wood adhesives [i.e., urea–formaldehyde (UF), melamine–urea–formaldehyde (MUF) resins, phenol–formaldehyde (PF), and phenol–resorcinol–formaldehyde (PRF) cold‐set resins, on lignocellulosic substrates (i.e., wood)] have recently been reported 6, 7. Such studies have been carried out because these resins are the most used (by volume) polycondensation resins to date, of which their main use is as thermosetting wood adhesives 8.…”
Section: Introductionmentioning
confidence: 99%
“…The gelation and vitrification curves are the most characteristic features of both TTT and CHT diagrams; the S‐shape of the CHT diagram, in particular, defines the region at which the reaction rate is greatly reduced because diffusion control becomes more pronounced in the glass‐transition region. Although the majority of the CHT and TTT diagrams studies reported to date have mostly focused on the curing of epoxy resins on glass fiber braid,1–5 CHT and TTT diagrams of other polycondensation resins used in considerable amounts as wood adhesives [i.e., urea–formaldehyde (UF), melamine–urea–formaldehyde (MUF) resins, phenol–formaldehyde (PF), and phenol–resorcinol–formaldehyde (PRF) cold‐set resins, on lignocellulosic substrates (i.e., wood)] have recently been reported 6, 7. Such studies have been carried out because these resins are the most used (by volume) polycondensation resins to date, of which their main use is as thermosetting wood adhesives 8.…”
Section: Introductionmentioning
confidence: 99%
“…Water solutions of commercial polyflavonoid tannin extracts of mimosa (Acacia mearnsii) bark tannin extract, natural quebracho (Schinopsis balansae) wood tannin extract, pine (Pinus radiata) bark tannin extract, and pecan (Carya illinoensis) nut membranes tannin extract and, furthermore, a quebracho tannin extract modification from which all carbohydrates had been eliminated (quebracho QS) by organic solvent extraction and a quebracho tannin adhesive intermediate treated according to viscosity-reducing and reactivityenhancing techniques already reported, the origins of which were, respectively, from Brazil, Argentina, Chile, United States, Italy, and, again, Argentina, were prepared, respectively, at a 50, 42, 35,36,45, and 45% extract solids concentration in water. The tannin extracts are produced industrially by countercurrent extraction with just water at 95°C in the case of mimosa, by countercurrent extraction with, respectively, 5 and 2% sodium sulfite and at 100 and 70°C for quebracho and pine tannin extracts, respectively, and by countercurrent extraction with 2-4% sodium sulfite and 0.4% sodium carbonate for pecan nut tannin extract.…”
Section: Methodsmentioning
confidence: 99%
“…The curves based on the equation without the 1/3 exponent appear to be closer to reality with still a very rapid but more moderate increase of p, followed by a slowing down of its growth due to the appearance of diffusional problems at degrees of conversion higher than 0.9, confirming a limit already determined by TTT diagrams built using different techniques. 6,34,35 In the case of the reaction of a polyflavonoid tannin and formaldehyde, it is then eq. (13) which needs to be used for the calculation of the degree of conversion p after the gel point:…”
Section: After the Gel Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature–time–transformation (TTT) curing diagrams and continuous heating transformation (CHT) curing diagrams of melamine–urea–formaldehyde (MUF) polycondensation resins, cured on a wood substrate were recently described 1. While the general trends of these diagrams have been clearly identified and described, what is needed for the CHT diagrams, more technologically significant for wood‐adhesive application, is to determine which manufacturing parameters influence the trends and the values of the time and temperature of the diagram.…”
Section: Introductionmentioning
confidence: 99%